Morphological Diversity of F1 Ornamental Chili Generation from Single Cross Hybridization - Aziza, Elea Nur; Anam, Khoirul; Khoiriyah, Annisa (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Ornamental chilli (Capsicum annuum L.) belongs to the Solanaceae family and is highly popular for its aesthetic value. Ornamental chilli plants are edible, with attractive plant architecture and fruit shapes, as well as varying levels of spiciness. The most preferred traits in ornamental chilli plants include compact size (suitable for potted plants), diverse and unique fruit shapes and colors, and upright fruit orientation. This study aims to investigate the morphological diversity in the F1 generation resulting from a single cross-hybridization between two ornamental chilli varieties, namely the Medusa Pepper, known for its compact growth habit, and the Black Pearl Pepper, characterized by purple-coloured fruits and leaves. Analysis of the qualitative data shows that the F1 generation shares a high degree of morphological similarity with the female parent, Black Pearl Pepper, with a similarity value exceeding 75%, while it exhibits no significant resemblance to the male parent, Medusa Pepper, with a similarity value of 0%. The F1 generation from the single cross demonstrates limited morphological variation, with all observed traits being largely influenced by dominant characteristics, including fruit color, plant habit, and leaf color.